Enterobacter sp. E1 increased arsenic uptake in Pteris vittata by promoting plant growth and dissolving Fe-bound arsenic. (July 2023) - Li, Aiting; Lu, Yingying; Zhen, Da; Guo, Ziheng; Wang, Gejiao; Shi, Kaixiang; Liao, Shuijiao
Abstract: Microbes affect arsenic accumulation in the arsenic-hyperaccumulator Pteris vittata, but the associated molecular mechanism remains uncertain. Here, we investigated the effect of Enterobacter sp. E1 on arsenic accumulation by P. vittata . Strain E1 presented capacities of arsenate [As(V)] and Fe(III) reduction during cultivation. In the pot experiment with P. vittata, the biomass, arsenic content, and chlorophyll content of P. vittata significantly increased by 30.03%, 74.9%, and 112.1%, respectively. Strikingly, the water-soluble plus exchangeable arsenic (WE-As) significantly increased by 52.05%, while Fe-bound arsenic (Fe–As) decreased by 29.64% in the potted soil treated with strain E1. The possible role of activation of arsenic by strain E1 was subsequently investigated by exposing As(V)-absorbed ferrihydrite to the bacterial culture. Speciation analyses of As showed that strain E1 significantly increased soluble levels of As and Fe and that more As(V) was reduced to arsenite. Additionally, increased microbial diversity and soil enzymatic activities in soils indicated that strain E1 posed few ecological risks. These results indicate that strain E1 effectively increased As accumulation in P. vittata mainly by promoting plant growth and dissolving soil arsenic. Our findings suggest that As(V) and Fe(III)-reducer E1 could be used to enhance the phytoremediation of P. vittata in arsenic-contaminated soils. Graphical abstract: Image 1 Highlights: Strain E1 presented capacities of As(V) and Fe(III) reduction during cultivation. The bioaccumulation of arsenic in Pteris vittate was enhanced by strain E1. Strain E1 increased the WE-As content and reduced the Fe–As content in soil. Strain E1 catalyzed As(V) and Fe(III) reduction on As(V) absorbed ferrihydrite. Strain E1 alleviated the negative effect of As on plant and soil health.